Toponomastic in Cuba. Morphosyntactic description in names of kindergartens (Islas, 2021)
In a previous study on Cuban toponomastics, the semantic and pragmatic springs that, among the names of the institutions, motivated the denomination of kindergartens, have been marked. The study warned about the need to extend the analysis to other levels, which is why this work intends to deal with, in the same object, certain distinctive morphosyntactic phenomena: its structure, derivation, interpretations of the plural and determination. Theoretical, empirical and specialized methods were applied, as well as grammatical analysis techniques with a descriptive and functional approach in order to address the significance of the mechanisms identified in the naming of these preschool education centers. The results also contribute to the description of the variant of Spanish spoken on the island.
Keywords: toponomastics; morphosyntax; kindergarten; determinant; derivation; plural